Pelatihan Penggunaan Aplikasi Keuangan Pada UMKM Gerabah Natar - Dwi Tirta Kencana; Aisyah Dzun Nuraini; Amanda Maylan Indriani; Ayu Novalinda Prayitno (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Technology can support business in: marketing strategies, product management, financial management that requires dedication even though the business looks simple, therefore the field of micro, small, and medium enterprises (UMKM) requires computer technology-based tools to carry out good business management by utilizing the Qasir Application. The Qasir application is a service provider to manage Point Of Sales products and services for UMKMs as an application of technology in business, this needs to be known by students of the Universitas Teknokrat Indonesia and communities. The purpose of this activity is to introduce the benefits of the Qasir Application to manage stock of goods, payments, financial management and reports on purchases and sales that can be accessed through Smartphones so that it is practical and accessible to many users simultaneously. The method of selling the material is by providing direct counseling and practice to the owners and employees of Pottery Crafts which is carried out according to the schedule directly, resulting in 98% good achievement for 6 people who were obtained after completing the material.